2022
DOI: 10.1007/978-3-031-15559-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use of Non-fungible Tokens (NFTs) as a Trading Mechanism for the Metaverse

Abstract: The notion of a metaverse seems hard to define but encourages the impression that it can be considered as a new virtual metaphysical landscape that somehow goes beyond our geographical locations and understanding (i.e., independent of time and space). Based on virtual reality, augmented reality, and blockchain, it is envisioned as an independent but extended world that is planned to be a digital virtuality entrenched not only in our old habits such as gaming and entertainment but also in virtual asset trade. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…of a physical asset (Yilmaz et al, 2022), NFT reinforces security in asset management in the metaverse due to its unique character and its inability to be exchanged by others (Buchholz et al, 2022;Y. Huang et al, 2023) In addition, NFTs open new doors to creativity and training in the metaverse (García R et al, 2023) "Digital artists have found in NFTs a platform to display and market their art in virtual galleries, allowing buyers to transparently follow copyright and associated terms of use."…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations

Blockchain paradigm in the metaverse

Arteaga Medranda,
Alcívar Cedeño,
Arteaga Delgado
et al. 2023
COCIRI
“…of a physical asset (Yilmaz et al, 2022), NFT reinforces security in asset management in the metaverse due to its unique character and its inability to be exchanged by others (Buchholz et al, 2022;Y. Huang et al, 2023) In addition, NFTs open new doors to creativity and training in the metaverse (García R et al, 2023) "Digital artists have found in NFTs a platform to display and market their art in virtual galleries, allowing buyers to transparently follow copyright and associated terms of use."…”
Section: Resultsmentioning
confidence: 99%
“…These units of value have the versatility to represent both physical and digital assets on the blockchain (Song & Qin, 2022). Whether it is a currency, a digital good, or even ownership of a physical asset, tokens enable a unique and transferable representation of value in the digital space (Ritterbusch & Teichmann, 2023;Yilmaz et al, 2022). This feature is integrated into various applications, from creating digital currencies to tokenizing real-world assets.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation

Blockchain paradigm in the metaverse

Arteaga Medranda,
Alcívar Cedeño,
Arteaga Delgado
et al. 2023
COCIRI
“…References [59,60] discussed the application of NFT in the metaverse from an economic point of view, and pointed out the importance of metaverse forensics. References [61,62] studied the possibility of using machine learning for metaverse forensics from a technical perspective.…”
Section: Non-fungible Tokens (Nfts) In Metaverse Forensicsmentioning
confidence: 99%
“…Metaverse unlocked the vision of virtual reality and how physical interaction could be imitated with the help of technology. Some prime examples include Fortnite's virtual concert featuring Marshmello and Lil Nas X's performance in Roblox [14].…”
Section: Introductionmentioning
confidence: 99%